Serum eosinophilic cationic protein: A marker of eosinophilic infiltration in inflammatory bowel disease? - Gülen ARSLAN; Mehmet CİNDORUK and Gül B. Ülkar and İ. Safa YILDIRIM (Turkish Journal of Gastroenterology, 2019)
-